Design and implementation of an open source android mobile barcode inventory software for the University of the Philippines Diliman School of Economics Library - Miclat, John Ezekiel D. (2015)
This thesis aimed to augment the prevailing inventory procedures of the University of the Philippines - School of Economics Library by producing an Android mobile inventory software which makes of barcodes affixed on the materials as unique identifiers. It was necessary to produce and implement the software due to the shortage of staff and the massive collection of the library.